A Review of the Discrete Element Method Application on Concrete Materials. (September 2020) - Ma'arif, F; Gao, Z; Li, F
Abstract: This paper describes an attempt to analyze each methodology and bring it all together in one place for crossreferencing expert analysis. The advantage of using DEM compared to continuum-based techniques is in cracking and fragmentation starting and spreading because the DEM system is naturally disconnected. Concrete is a non-homogeneous composite material with significant heterogeneity of quasi-brittle characters. Structural failure behavior in concrete usually preceded by initial cracking and influenced by the mesoscale structure, interface between aggregate and mortar matrix, especially under complex pressure conditions. The ability of the DEM to produce 3-phase material representation in concrete will significantly depend on the application of the contact model between particles that have bound during the simulation. The main development area in this paper is related to stages (particle contact, contact model), parameters, and implementation that are entirely established in the simulation phase of materials. It will assist future researchers in improving analysts when modeling concrete to select appropriate methods and procedures, and to identify critical parameters for specific applications.